Growth, innovation and reform in Eastern Europe - Gomulka, Stanislaw (Brighton, Sussex : Wheatsheaf Books : Distributed by Harvester Press, 1986)
This book is concerned with various aspects of the economy of the eastern Europe and the USSR
Includes bibliographical references.
oo 21/01/2019
Loans
Keywords: Economic growth; Economic history; Economic development; Europe, Eastern; Soviet Union